Institutions, credibility and crisis: The inconsistencies of Argentine exchange rate policy (1991-2006) - Cherny, Nicolas (2014)
The purpose of this article is twofold. The first is to explain the time inconsistencies of the convertibility regime that led to the 2001 crisis. The argument suggests that the credibility requirements for convertibility induced a dynamic of legal, fiscal, financial and external commitments that increased exit costs and time inconsistencies. The second objective is to explain the tensions of the floating regime that replaced convertibility in 2002. We describe the effects of a floating exchange rate on macroeconomic imbalance and the growing tension between competitiveness and inflation.